Isoflavon Kedelai Diperkaya dengan Zn sebagai Suplemen Antiarterosklerosis Wanita Premenopause - Winarsi, Hery (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2007)
This research was conducted to observe the effect of soy isoflavone and Zn on totalcholesterol, LDL, TG and HDL levels of premenopausal women. Thirty-threepremenopausal women in Purwokerto were given supplement containing soy isoflavoneand Zn during 2 months. In the control group (SO), 11 women were given placebo; inthe group SI, 11 women were given the supplement containing soy isoflavone; and in thegroup SIZ, 11 women were given the supplement containing soy isoflavone and Zn.Blood samples were taken 3 times, i.e. baseline, 1 and 2 month after intervention. Oneml of blood was taken by venoject-heparin, intravenously. Blood plasma was used todetermine total cholesterol, LDL, HDL, and TG levels using spectrophotometer. Dataobtained were analysed by ANOVA. The total cholesterol, LDL, and TG plasma levelsdecreased, from 189,27 to 151,63 mg/dl (p=0,02); from 138,97 to 93,93 mg/dl (p=0,004);and from 208,81 to 121,09 mg/dl (p=0,012) respectively. On the contrary HDL levelincreased, from 48,38 to 67,27 mg/dl (p=1,72E-05) after 2 months of intervention. Soyisoflavone and Zn (SIZ) have potential as antiatherosclerosis supplement.